Who gains from credit granted between firms? Evidence from inter-corporate loan announcements made in China - Qing He; Liping Lu; Steven Ongena (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Who gains from inter-corporate credit? To answer this question we measure the impact of the announcements of inter-corporate loans in China on the stock prices of the firms involved. We find that the average abnormal return for the issuers of inter-corporate loans is significantly negative, whereas it is positive for the receivers. Issuing firms may be perceived by investors to have run out of worthwhile projects to finance, while receiving firms are being certified as creditworthy. Subsequent firm performance and investment confirms these valuations as overall accurate.
urn:nbn:de:hebis:30:3-395767
Keywords: G30; G14; G21; 330; entrusted loan; inter-corporate loan; credit misallocation; certification